We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
173
1
avatar

Here's the series: I took what I was given into the \(S_n = {a(1 - r^{n}) \over 1 - r}\) formula where:

 

\({S_n}\) is the sum of \({n}\) number of terms

\({a}\) is the first term

\({r}\) is the common ratio

 

Here's my work:But I didn't get the answer, which is

I'm confused as to what did I do wrong?

 Jul 9, 2018
 #1
avatar
0

Sum =6 x [1 - 3/2] / [1 - 3/2]

Sum =6 x [1 - 59,049 /1024] / [ - 1/2]

Sum =6 x [-58,025 /1,024] / [-1/2]

Sum =6 x [-58,015/1,024 x -2/1]

Sum =6 x [116,050/1,024]

Sum = 696,300 / 1,024       divide both sides by 4

Sum = 174,075 / 256

 Jul 9, 2018

13 Online Users